2021
DOI: 10.3389/fmed.2021.710992
|View full text |Cite
|
Sign up to set email alerts
|

Case Reports: Bronchial Mucosal Vasculature Is Also Involved in the Acute Vascular Distress Syndrome of COVID-19

Abstract: Background: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) which targets the pulmonary vasculature is supposed to induce an intrapulmonary right to left shunt with an increased pulmonary blood flow. We report here what may be, to the best of our knowledge, the first videoendoscopic descriptions of an hypervascularization of the bronchial mucosa in two patients hospitalized for coronavirus disease 2019 (COVID-19) pneumonia.Cases Presentation: Two patients, 27- and 37-year-old, were addressed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This may be an underlying, unifying mechanism responsible for the widespread systemic manifestations seen with SARSCoV-2 infection ( 38 ). On this regard, also term “Acute Vascular Distress Syndrome” was introduced, to account for the quite unique vascular pathophysiology in COVID-19 pneumonia ( 17 , 18 ). A key feature reported is a low ventilation-to-perfusion ratio, leading to an increased pulmonary blood flow with intrapulmonary right to left shunt ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be an underlying, unifying mechanism responsible for the widespread systemic manifestations seen with SARSCoV-2 infection ( 38 ). On this regard, also term “Acute Vascular Distress Syndrome” was introduced, to account for the quite unique vascular pathophysiology in COVID-19 pneumonia ( 17 , 18 ). A key feature reported is a low ventilation-to-perfusion ratio, leading to an increased pulmonary blood flow with intrapulmonary right to left shunt ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed a potential link between COVID-19 and endothelial dysfunction. On this regard, also the term “Acute Vascular Distress Syndrome” was introduced, to account for the vascular pathophysiology in COVID-19 pneumonia ( 17 , 18 ). This comprises vasoplegia along with a reduced ventilation-to-perfusion ratio, leading to an increased pulmonary blood flow with intrapulmonary right to left shunt ( 18 ).…”
Section: Introductionmentioning
confidence: 99%